Discourse analysis as a method in strategy-as-practice - Vaara, Eero (Henry Stewart Talks, 2012)
Discursive perspectives on strategy, Strategy discourse, Narratives, Conversations, Strategic plans, Media texts, Discursive analysis of strategy, Strategy as multifaceted discourse, Interdiscursivity and recontextualization, Discourse and power in context, Discursive struggles, Discourse and materiality, Methodological questions